Adsorption study on the removal of copper from aqueous solution using activated durian (Durio zibethethinus murray) rinds - Viray, Maria Virginia Pilar M. (Manila : National University, 2020)
Activated Carbon (AC) is the furthermost popular and most commonly used adsorbent material. Because of the high price of commercial activated carbon and the growing increase in the demand for industrial wastewater treatment, low cost and efficient sources of activated carbon is essential parameters in selecting treatment alternatives.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Results and discussion -- Chapter 5. Summary, Conclusion and recommendation -- References -- Appendices.
Includes bibliographical references.